The Palgrave Handbook of Family Policy 2020
DOI: 10.1007/978-3-030-54618-2_23
|View full text |Cite
|
Sign up to set email alerts
|

Managing Work-Life Tensions: The Challenges for Multinational Enterprises (MNEs)

Abstract: Managing work-life issues presents a number of challenges for HR departments in multinational enterprises (MNEs) because of the complexity of implementing policies that require sensitivity to local issues such as cultural traditions and legislation. However, there has been limited discussion among researchers regarding the roles and responsibilities of HR managers in MNEs and even less attention given to work-life management in the global context. A tension-centered approach to analyzing these complexities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Comparative research on family policies offered by enterprises and their relationship with public policies is relatively recent, although growing (for example, den Dulk et al, 2018;Pavolini and Seeleib-Kaiser, 2018;Bardoel, 2021;Chung, 2021). But research on developing countries with less 'mature' family policies shows that the relationship between public and enterprise family policies may be more complex than a simple integration of the former by the latter, with the state regulating what enterprises should offer.…”
Section: Challenges Coming From Research On An Increasingly Diversifi...mentioning
confidence: 99%
“…Comparative research on family policies offered by enterprises and their relationship with public policies is relatively recent, although growing (for example, den Dulk et al, 2018;Pavolini and Seeleib-Kaiser, 2018;Bardoel, 2021;Chung, 2021). But research on developing countries with less 'mature' family policies shows that the relationship between public and enterprise family policies may be more complex than a simple integration of the former by the latter, with the state regulating what enterprises should offer.…”
Section: Challenges Coming From Research On An Increasingly Diversifi...mentioning
confidence: 99%
“…In recent years (that also include the devastating pandemic phase), a painful picture is observed that reflects that the well-being of employees is in jeopardy (Caligiuri et al, 2020;Jaiswal et al, 2022). The workforce is facing as well as handling complicated challenges without being able to adjust and cope emotionally (Bardoel, 2020). Work relationships are irrevocably disrupted yet they are striving to meet deadlines.…”
Section: Introductionmentioning
confidence: 99%